ICT-BASED KNOWLEDGE MANAGEMENT FOR INTERNSHIP PROGRAM STUDY CASE OF ATOURIN (The Indonesian Journal of Business Administration, 2021)
In today's digital era, phenomena such as the gig economy are one of the results of technological advances. Programs such as internships have now been carried out by many companies in order to maximize the business practices they run. Atourin is one of the start-up companies that are also running the program. In the end, the company's ability to maximize both the experience and knowledge gained from the program is a challenge in itself considering the large number of enthusiasts from the participants. This thesis focuses on finding the most suitable ICT-based knowledge management system for the company. The data collection carried out in this thesis uses a qualitative approach and direct observation by the author during an internship at the company. Through a data processing process that has a problem identification stage, then determining the purpose of solving the problem, identifying what knowledge is needed, and analyzing the core components of knowledge management, namely people, processes, and technology. All these processes are then completed using SECI to determine the flow of knowledge sharing. In the end, it was found that the interns developed more knowledge on the externalization process. This thesis also provides a plan for the implementation of the results of the research conducted in the last chapter. The plan takes 6 months with evaluation at the end of the process. Keywords: Knowledge Management, Gig Economy, Internship, SECI, PPT, ICT.